Trichaleurina javanica from West Java - Rudy Hermawan; Mega Putri Amelya; Za'Aziza Ridha Julia (Perhimpunan Mikologi Indonesia, 2020)
Trichaleurina is a fleshy mushroom with goblet-shaped within Pezizales. Many genera have a morphology similar to Trichaleurina, such as Bulgaria and Galiella. Some previous reports had been described fungi like Trichaleurina as Sarcosoma. Indonesia has been reported that has Trichaleurina specimen (the new name of Sarcosoma) by Boedijn. This research aimed to obtain, characterize, and determine the Trichaleurina around IPB University. Field exploration for fungal samples was used in the Landscape Arboretum of IPB University. Ascomata of Trichaleurina were collected, observed, and preserved using FAA. The specimen was deposited into Herbarium Bogoriense with collection code BO 24420. The molecular phylogenetic tree using RAxML was used to identify the species of the specimen. Morphological data were used to support the species name of the specimen. Specimen BO 24420 was identified as Tricahleurina javanica with 81% bootstrap value. Molecular identification was supported by the morphological data, such as the two oil globules and the size of mature ascospores.